Public spending on health as political instrument? Regime-type dependency of public spending - Angela Münch; David Fielding; Andreas Freytag (Open Economics, 2020)
The paper argues that the level of public spending on health varies according to the type of political regime in a country. A simple political economic model is employed to analyse the rationale of policy makers when implementing healthcare policy. The theory of dictatorship as described by Wintrobe (1990, 1998, 2001) is used to differentiate between the types of autocratic regimes. Furthermore, an empirical analysis is conducted for 170 countries for the years 1995- 2014. We found that public spending on health is decreasing with the level of political freedom. At the same time, public spending on health care competes with military expenditures. Moreover, public spending on health in neighbouring countries affects the level of public spending within the country.
Keywords: I18; H51; 330; public spending; health regime; selection effect; Wintrobe